Case Report of Subclavian Artery Injury After Reduction of Right Shoulder Dislocation - Rodrigues, Mariana Ferreira Borges Firmo; Rodrigues, Emanuel Firmo; Andreazza, Nathalia; Alves, Lívia Coelho; Mendes, Pedro Natel Kugler (Brazilian Journal of Case Reports, 2025)
Shoulder dislocations are common in emergency settings; however, associated vascular injuries are rare, occurring in approximately 1–2% of cases. Among these, axillary and subclavian artery damage is particularly serious, with high morbidity and potential limb loss if not promptly recognized. We report the case of a 79-year-old male, hypertensive and dyslipidemic, who sustained a ground-level fall with right glenohumeral dislocation. Following an attempted closed reduction without sedation, he developed ischemic signs and an expanding hematoma. Initial workup with non-contrast tomography and bedside ultrasound suggested subclavian artery thrombosis. During brachial artery embolectomy, a complete subclavian artery rupture with a 7 cm gap was identified, requiring open repair with a 6 mm Dacron® graft. Postoperatively, the patient developed significant motor deficits of the right upper limb, confirmed by MRI and electromyography as brachial plexus injury. He was discharged on anticoagulation and remains under follow-up with partial functional recovery. This case highlights the importance of systematic neurovascular examination in shoulder dislocation, especially in elderly patients with comorbidities, as collateral circulation may mask early ischemia. Early use of contrast imaging and standardized emergency protocols are critical to improving outcomes. Although rare, subclavian artery injury during shoulder reduction must always be considered, requiring immediate diagnosis and intervention to preserve limb viability and function.